Slithering snakes, angry men and out-group members: What and whom are we evolved to fear? - Mallan, K.; Lipp, Ottmar; Cochrane, B. (Routledge, 2013)
The preparedness theory of classical conditioning proposed by Seligman (1970, 1971) has been applied extensively over the past 40 years to explain the nature and “source” of human fear and phobias. In this review we examine the formative studies that tested the four defining characteristics of prepared learning with animal fear-relevant stimuli (typically snakes and spiders) and consider claims that fear of social stimuli, such as angry faces, or faces of racial out-group members, may also be acquired utilising the same preferential learning mechanism. Exposition of critical differences between fear learning to animal and social stimuli suggests that a single account cannot adequately explain fear learning with animal and social stimuli. We demonstrate that fear conditioned to social stimuli is less robust than fear conditioned to animal stimuli as it is susceptible to cognitive influence and propose that it may instead reflect on negative stereotypes and social norms. Thus, a theoretical model that can accommodate the influence of both biological and cultural factors is likely to have broader utility in the explanation of fear and avoidance responses than accounts based on a single mechanism.